Interactions between fire and introduced deer herbivory on coastal heath vegetation. (25th February 2016) - Crowther, Mathew S.; Ortac, Geetha; Pedersen, Simen; McArthur, Clare
Abstract: The coastal heathlands of the Royal National Park are impacted by both fire and herbivory by introduced deer, and to date these two factors have been dealt with independently in the management of natural areas. In recent years, there has been increasing recognition for a more integrated approach to manage these two disturbance agents. Fire and its role in Australian heathlands are well known, while impacts from introduced deer and the combined effects of fire and introduced deer are still poorly understood. In this study, we investigated the effects of fire and Javan rusa deer ( Cervus timorensis ) on both vegetation cover and floristics. The percentage cover of plants at different height layers and the presence/absence of individual species were recorded at sites representing two different burn histories (1993/1994 and 2000/2001) and deer presence or absence. Fire significantly reduced vegetation cover at low (<50 cm) and intermediate heights (50–100 cm), while deer presence affected grasses and sedges, and low vegetation at more recently burnt sites. Rusa deer also affected composition of the plant species assemblages, but no such effect was found for fire. Understanding the influence of each disturbance factor independently and together in the heathlands will be critical for implementing a more robust framework for future management.